As time goes by: 20 years of changes in the aquatic macroinvertebrate metacommunity of Mediterranean river networks. (5th July 2020) - Cañedo‐Argüelles, Miguel; Gutiérrez‐Cánovas, Cayetano; Acosta, Raúl; Castro‐López, Daniel; Cid, Núria; Fortuño, Pau; Munné, Antoni; Múrria, Cesc; Pimentão, Ana Rita; Sarremejane, Romain; Soria, Maria; Tarrats, Pol; et al.
Abstract: Aim: To analyse temporal metacommunity dynamics in river networks in relation to hydrological conditions and dispersal. Location: Fifteen river reaches from the Llobregat, Besòs and Foix catchments in the North‐Eastern Iberian Peninsula. Taxon: Aquatic macroinvertebrates belonging to 99 different families. Methods: We sampled aquatic macroinvertebrate communities during spring in 20 consecutive years. We built two environmental distances (one related with water chemistry and another one with river flow regime) and two spatial distances (network distance and topographic distance). Then we used Mantel tests (accounting for spatial autocorrelation) to relate macroinvertebrate dissimilarity with environmental and spatial distances. Additionally, we determined the dry and wet years using the Standardized Precipitation Index (SPI) and we classified macroinvertebrate families based on their ability to fly and to drift. Finally, we ran a linear regression model including the correlation value ( r ) of each Mantel test as response variable and distance type (environmental or spatial), SPI, dispersal mode, their pairwise interactions and a three‐way interaction as predictor variables. Results: Metacommunity organization varied over time and it was significantly affected by precipitation, which can be related to river network connectivity. The environmental filters, mainly the flow regime, were generally more important than the spatial filters in explaining community dissimilarity over the study period. However, this depended on the dispersal abilities of the organisms. Network fragmentation due to flow intermittence during the dry years significantly reduced the dispersal capacity of strong aerial dispersers, leading to spatially structured metacommunities. For strong drift dispersers, community dissimilarity patterns were generally best explained by environmental filters regardless of SPI. Main conclusions: A significant temporal variation in metacommunity organization can be expected in highly dynamic systems (e.g. Mediterranean rivers) and it might depend on the dispersal modes and abilities of the organisms, since they determine the response to changes in environmental and landscape filters.